Hakekat Beban Pembuktian Terbalik Terhadap Pencucian Uang Di Indonesia - Widhy Andrian Pratama; Halimah Endang Widyaningsih (Jurnal Hukum Ekualitas, 2026)
Money laundering is categorized as an extraordinary crime, so its prevention requires an unconventional approach in the form of extraordinary measures. The provisions of Article 69 of Law No. 8 of 2010, are a manifestation of this approach, by allowing the process of investigation, prosecution, and examination of cases in court to be carried out without having to first prove the original crime. The author conducted this research with a data-based approach through a literature study method. Data were collected through a review of various relevant sources, such as journals, books, articles, and similar references. Information from print and digital media related to the topic was also used as part of the research data. The approach in normative law focuses on efforts to understand the basics and scope of law as a system that reflects social reality. This study consists of two main elements, namely the analytical and normative dimensions, which together describe the fundamental nature of law. From this research, the author concludes that in money laundering cases, although the burden of proof generally rests with the defendant, this does not relieve the public prosecutor of the responsibility to prove that the assets charged are indeed derived from a criminal act. Therefore, the evidentiary process is a shared responsibility, with the defendant, investigator, public prosecutor, and judge each having a role commensurate with their respective responsibilities. The system of reversal of the burden of proof applied is limited or balanced, meaning that both parties, the public prosecutor and the defendant, bear a proportionate burden of proof. However, in practice, this principle is often not applied consistently, so the burden of proof remains based on the conventional system stipulated in the Criminal Procedure Code.